Is Surgical Removal of Asymptomatic Third Molars in the Horizontal III-C Position Advisable? A Pilot Study of Tomographic Evaluation - João Paulo da Silva Guilherme; Marcelo Santos Bahia; Yuri de Lima Medeiros; Marcella Yumi Kadooka; Marcelo Tarcísio Martins; Isabel Cristina Gonçalves Leite; Marcos Vinicius Queiroz de Paula (Stilus Optimus, 2024)
Objectives: This cross-sectional study aimed to measure the distance between the buccal and lingual cortical bones and its relation with the mandibular canal roof of third molars classified as III-C position according to Winter, Pell and Gregory classifications in cone-beam computed tomography. Material and Methods: A total of 140 lower third molars were classified according to Winter, Pell and Gregory. The distance between the buccal external cortex and the lingual external cortex was measured at 25%, 50% and 75% of the distance to the roof of the mandibular canal in parasagittal sections of teeth classified in horizontal III-C position. The presence or absence of lesions associated with the elements in this position was observed. Descriptive statistical analysis was performed and the intra-examiner agreement was calculated using the Bland-Altman and t-test methods (0.88 and 0.91, respectively). The significance level used was 5% (P ≤ 0.05). Results: Seventy patients (29.4 [SD 8.8] years, 54% women and 46% men) were included. Fourteen (10%) third molars were classified in horizontal III-C position. The average measurements taken were 1.78, 1.1 and 1.53 mm for the distances between the buccal external cortex and lingual external cortex, at 25%, 50% and 75% of the distance to the roof of the mandibular canal, respectively. No pathological conditions associated with the included elements were observed. Conclusions: Analysis of cone-beam computed tomography parasagittal sections of third molars classified in horizontal III-C position, revealed proximity of impacted teeth to the mandibular canal roof, mainly in the midline between the buccal and lingual external cortices.